Tinjauan Yuridis Terhadap Pengalihan Objek Jaminan Fidusia Tanpa Persetujuan Kreditur - Muhammad Hafidz Syafiuddin; Fransiscus Xaverius Arsin Lukman (Jurnal USM Law Review)
This study discusses the credit agreement of banking and non-banking financial institutions requiring the existence of a collateral that must be done first in order to be able to make credit. A loan agreement with a fiduciary guarantee is the procedure chosen to adapt to the growth of the business world and the needs of the community. This research explains about the transfer of fiduciary collateral objects without the collector's approval and also about the application of legal protection in the practice of fiduciary engagements to the collectors. The borrower must have good intentions to properly maintain the collateral. About Fiduciary collateral, borrowers are not allowed to exchange, loan or lease to other parties for goods that are used as objects of fiduciary collateral, if the collecting party does not agree. It is legally valid that the fiduciary giver has taken an action that diverts the object of the fiduciary collateral being carried out, if the party receiving the fiduciary does not give written consent. The practice of legal protection for creditors has not yet reached the maximum point, this is because there are still many factors that put emphasis on creditors when they want to execute collateral objects themselves.